2017
DOI: 10.5380/avs.v22i4.56797
|View full text |Cite
|
Sign up to set email alerts
|

Approach to Homelessness Vulnerability and the Impact as One Health Initiative

Abstract: RESUMO: Pessoas em situação de rua têm sido consideradas um problema mundial na área da política pública e que demanda uma intervenção multidisciplinar com abordagem de assistência social e saúde. Algumas dessas pessoas em situação de rua têm interação próxima e de companhia com animais domésticos. Embora animais de companhia possam oferecer estabilidade emocional, podem contribuir para recusa no acolhimento humano e persistência nas ruas, como animais de companhia podem ser proibidos de adentrar em abrigos hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Pets in this population benefit from care and companionship outside of shelters and may have a stronger human‐animal bond compared with pets in stable housing (Taylor et al, 2004). However, conditions in which unhoused individuals live increase risk factors for certain zoonotic and ectoparasitic diseases (Gravinatti et al, 2017). Fleas, ticks and mosquitos transmit diseases such as bartonellosis, typhus, spotted fevers, anaplasmosis, ehrlichiosis, Lyme disease, heartworm and West Nile fever.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pets in this population benefit from care and companionship outside of shelters and may have a stronger human‐animal bond compared with pets in stable housing (Taylor et al, 2004). However, conditions in which unhoused individuals live increase risk factors for certain zoonotic and ectoparasitic diseases (Gravinatti et al, 2017). Fleas, ticks and mosquitos transmit diseases such as bartonellosis, typhus, spotted fevers, anaplasmosis, ehrlichiosis, Lyme disease, heartworm and West Nile fever.…”
Section: Introductionmentioning
confidence: 99%
“…Public perception of pet ownership in the unhoused population tends to be negative (Irvine et al, 2012), despite recent evidence suggesting that unhoused pets are in similar health conditions as housed pets (French et al, 2021). Many shelters and affordable housing units prohibit pets (Gravinatti et al, 2017; Wusinich et al, 2019), yet one study found that 93–96% of unhoused pet owners would not accept housing if their pets were not allowed (Singer et al, 1995). This obstacle prevents many unhoused individuals from finding suitable housing without killing the strong bond they share with their pets.…”
Section: Introductionmentioning
confidence: 99%